2023
DOI: 10.3390/vaccines11061124
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with College Students’ Human Papillomavirus (HPV) Vaccination and Preferred Strategies for Catch-Up Vaccine Promotion: A Mixed-Methods Study

Abstract: Human papillomavirus (HPV) vaccination protects against six types of cancer—cervical, anal, oropharyngeal, penile, vulvar, and vaginal. In the United States (U.S.), HPV vaccination coverage in college students remains low, especially in the Mid-South region, despite the highest risk of HPV infections and disease burden. However, few studies have assessed HPV vaccination among college students here. This study examined factors associated with HPV vaccination among college students in the Mid-South and explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…In a 2022 study of HPV vaccination rates in states, Iowa had the fourth highest uptake among states, with 74.9% of adolescents aged 13–17 years having received the HPV vaccine [ 19 ]. In a 2023 study of 417 Mid-South college students aged 18–26 years, 48.7% of students had been vaccinated for HPV, and 53% of females had received at least one dose of the vaccine [ 13 ]. The increased rate of vaccination of students surveyed in this study may be explained by Iowa having a higher uptake of the vaccine than many other states; however, the surveyed students had a higher vaccination rate than the Iowa average as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 2022 study of HPV vaccination rates in states, Iowa had the fourth highest uptake among states, with 74.9% of adolescents aged 13–17 years having received the HPV vaccine [ 19 ]. In a 2023 study of 417 Mid-South college students aged 18–26 years, 48.7% of students had been vaccinated for HPV, and 53% of females had received at least one dose of the vaccine [ 13 ]. The increased rate of vaccination of students surveyed in this study may be explained by Iowa having a higher uptake of the vaccine than many other states; however, the surveyed students had a higher vaccination rate than the Iowa average as well.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there have been no studies on HPV vaccine uptake and perceptions in large Midwest universities. Similar studies in the US in the South and Mid-Atlantic have found HPV vaccine uptake and HPV knowledge to be low in university students [13,14]. The objective of this study was to determine the uptake and perceptions of the HPV vaccine in students enrolled at the University of Iowa.…”
Section: Introductionmentioning
confidence: 86%
“…Each of the surveys consisted of items and instruments developed by the research team based on prior research ( 27 , 28 ) and experience and also based on published available items and surveys. In some instances, items were adapted for the study to focus on selected vaccinations and the population being studied.…”
Section: Methodsmentioning
confidence: 99%
“…This warrants concern as people who are classified as vaccine-hesitant may have different or similar motivations and informational needs across vaccines ( 23 ) which could be overlooked in intervention development, limiting effectiveness. Furthermore, vaccine concerns change over time and should be monitored for changes in vaccination attitudes and behaviors for different vaccines ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Italy in 2022, HPV vaccination coverage was clearly inadequate, as was adherence to screening, both far from WHO targets [ 7 ]. Studies have identified perceived barriers to vaccination among the student population[ 8 ] as well as among health care workers and teachers[ 9 ], including mistrust of the vaccine due to its perceived novelty, low knowledge, and misinformation about the vaccine. A Chinese study found in 2015 that educational intervention on HPV increased awareness regarding HPV and women’s intention to vaccinate themselves[ 10 ].…”
Section: Introductionmentioning
confidence: 99%